Pump power depreciation by photodarkening in ytterbium-doped fibers and amplifiers - Li, Nanxi (2014)
In this letter, pump power depreciation due to photodarkening effects in an ytterbium doped fiber (YDF) is investigated. Photodarkening is monitored by measuring the transmitted power at visible and pump wavelengths simultaneously, which renders direct quantitative measurement of pump power reduction rather than excess background loss. Our observation of substantial reduction in the pump power and the shortened fluorescence decay time in the photodarkened fiber indicates that the photodarkening influences pump efficiency. The effect of the photodarkening in a device level is also investigated by observing the performance of the YDF amplifier implementing the same YDF. The pump power depreciation of this fiber amplifier is quantitatively investigated by numerical simulation. The results suggest that operating at a saturated regime helps to subdue the photodarkening, with explanation in terms of population inversion density provided. The level of power depreciation is calculated to be 15%-30%, which matches our experimental observation